All the World's a Con: Frontstage, Backstage, and the Blurred Boundaries of Cosplay. Issue 4 (29th December 2020) - Masi de Casanova, Erynn; Brenner‐Levoy, Jeremy; Weirich, Cole
Abstract : Through participant observation and interviews with cosplayers in the midwestern United States, we analyze the boundaries between frontstage and backstage and between self and persona (character) in cosplay spaces, where fans dress up as fictional characters. We find that back and front regions bleed into each other without causing the conflict or tension that dramaturgical theorists would predict, and that cosplayers engage in varying degrees of theatrical performance when in costume. This blurring of boundaries between front/back and self/character is part of what makes cosplay pleasurable. We argue that the body—not just as a "personal front, " but as cosplayers experience it—is important for understanding what cosplayers mean when they talk about "becoming someone else."